Arab and Muslim contributions to Medicine and Research A Review (Bangladesh Journal of Medical Science, 2017)
The accomplishments in the development of knowledge by medieval Arab civilization have been termed by some scholars as mere translation and preservation of Greek knowledge. It is alleged that the original works of Arab were only the preservations and duplications. They had no curiosity for learning and thus their insights, intuitions and cognition were immature. And it is assumed that investigations and inquiries are the achievement of recent periods. This study intends to investigate the knowledge expansion in the perspective of research in field of medicine by the Arabs. There are many renowned scholars who had made such irresponsible comments regarding Arabian diligence. For instance E.G. Brown comments its long recognized importance, lies not in its originality, but in the fact that in the long interval which separated the decay of Greek learning from the Renaissance, it represented the most faithful tradition of ancient wisdom, and during the dark ages was the principal source from which Europe derived such philosophical and scientific ideas as it possessed. Thus such paradigm statement was largely propagated by the scholars who had limited access to the Arabic literature. In contrast the fact is that initial Arabian contribution in the knowledge was the golden period of Arabs. The investigation based upon the reliable classical and historical literature revealed that the Arabs emphasized on research and rational thinking as their important tools of growth and development in medicine as could be observed in Al-Razi statement any physician who is dependent only on his experimentation and neglect literary knowledge and hypothesis then he may be a failure. Hence, an attempt is made to explore and highlight the Arab endeavors in original medical innovations which made them the sole source of many learning scholars. They had excelled in many innovations like bed side clinics, differential diagnosis between small pox and measles, concepts of mobile clinics, pharmacy, emergency facilities, midwifery, separate pediatrics facilities and advancement in the fields of psychiatry, cardiology, ophthalmology etcBangladesh Journal of Medical Science Vol.16(3) 2017 p.339-345